Module Development of Project-Based Learning to Increase Student Independence and Study Results in Disruption Era - Dwi Silviani Zulianingtiyas; Gres Dyah Kusuma Ningrum (International Research and Development for Human Beings (IRDH), 2024)
Learning in the era of disruption requires the development of innovation in various sectors. No exception in the education field. At SMKN 6 Malang, it requires the development of modules to support students' independent learning, so that learning materials can be delivered completely. This research is about research and development that aims to design, develop, and test the subject module of simulation and digital communication with project-based learning content for 10th grade students at SMKN 6 Malang using the 4D method. The sequence in this development begins with the definition, design, development, and dissemination stages. Furthermore, the product results were tested on 10th grade students majoring in RPL at SMKN 6 Malang, and there was an increase in study results and student independence. The results of the research conducted on experts and trials on students were: validation of feasibility from media experts obtained an average percentage score of 90.94%; validation of feasibility from material experts obtained an average percentage score of 86.29%. Individual trials by 3 students obtained an average percentage score of 80.95%; small group trials by 7 students obtained an average percentage score of 82.14%; and large-scale trials conducted by 23 students obtained an average percentage score of 85.09%. Overall, this module is declared Very Good/Very Eligible for use in the learning process. This study also showed an increase in learning completion values from before to after using the module. The results obtained were an increase of 8-12% and were declared effective. Furthermore, the learning independence in this study obtained an average percentage value of 81.56%, which in this study was very high.